2009
DOI: 10.1523/jneurosci.2672-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Compartment and Neuronal Output Mode Determine Pathway-Specific Long-Term Potentiation in the Piriform Cortex

Abstract: The apical dendrite of layer 2/3 pyramidal cells in the piriform cortex receives two spatially distinct inputs: one projecting onto the distal apical dendrite in sensory layer 1a, the other targeting the proximal apical dendrite in layer 1b. We observe an expression gradient of A-type K ϩ channels that weakens the backpropagating action potential-mediated depolarization in layer 1a compared with layer 1b. We find that the pairing of presynaptic and postsynaptic firing leads to significantly smaller Ca 2ϩ signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 51 publications
(87 reference statements)
5
58
0
1
Order By: Relevance
“…Experiments followed approved national and institutional guidelines for animal use. Acute slices of the aPC (400 m thickness) were prepared from Wistar rats of either sex (age, postnatal days 18 -25) in a coronal plane perpendicular to and containing the LOT (Johenning et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments followed approved national and institutional guidelines for animal use. Acute slices of the aPC (400 m thickness) were prepared from Wistar rats of either sex (age, postnatal days 18 -25) in a coronal plane perpendicular to and containing the LOT (Johenning et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The stimulation electrode was placed in layer 1a, ventrally between the LOT and the imaged field of view (i.e., toward the LOT). Intracortical inputs were selectively blocked by 30 M baclofen (Tang and Hasselmo, 1994;Franks and Isaacson, 2005;Johenning et al, 2009). Stimulation strength was adjusted to be at the threshold for activation of at least one cell in the population with two stimuli.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has so far identified, for example, classes of glutamate-releasing principal neurons (Franks and Isaacson, 2006;Suzuki and Bekkers, 2006), their dendritic properties (Bathellier et al, 2009), circuits and synaptic plasticity (Franks and Isaacson, 2005;Poo and Isaacson, 2007;Johenning et al, 2009), and classes of GABA-releasing interneurons and their circuits (Young and Sun, 2009;Stokes and Isaacson, 2010;Suzuki and Bekkers, 2010a,b). We have previously reported that the main input layer of the PC, layer II, contains two functionally distinctive kinds of principal neurons, semilunar (SL) and superficial pyramidal (SP) cells (Suzuki and Bekkers, 2006).…”
Section: Introductionmentioning
confidence: 99%